CO2 storage options in development of CCUS value chain scenarios in northern Poland - Wójcicki, Adam (Frontiers in Earth Science, 2025)
This study builds on the findings of the CCUS ZEN project by focusing on the local storage options of one of the value chains considered in that study, located in the region of northern Poland. Storage options include potential sites in saline aquifers, both onshore and offshore, which have already been screened, selected and evaluated in previous domestic and European projects. The reservoir and caprock parameter data from the literature has been harmonised and validated. The associated uncertainties, knowledge gaps and risks have also been addressed. The standard CSLF methodology for estimating volumetric (static) storage capacity and the Monte Carlo method were used. The storage efficiency factor was then estimated using data on CO2 injection simulations from the literature. Taken together, these steps go beyond the evaluations carried out in previous projects for these sites. The study shows that deploying and developing such a relatively immature value chain necessitates the integration of technical and non-technical elements, such as legal, social, and policy frameworks. Its focus is specifically on using the local potential for CO2 storage as an alternative and supplementary measure to shipping. For CCUS planning in Central Europe, it is important that the value chain includes a CO2 import-export terminal in the Port of Gdańsk. This terminal will eventually be connected to offshore and onshore storage sites via pipelines. The value chain could also be expanded to connect more emission sources and storage sites. This could potentially form part of future regional and pan-European CO2 storage and CCS infrastructure.